Fatigue crack growth in a material with coarse brittle phases. (February 2020) - Riedel, Hermann
Graphical abstract: Highlights: Analytical solution for fatigue crack growth in ductile materials with brittle phases. Numerical method for transient crack growth in a field of brittle particles. Depending on their fracture toughness brittle particles pin or accelerate the crack. Experiments reported in the literature confirm the conclusions drawn from the model. Abstract: The paper explores the effect of brittle particles on fatigue crack growth. A model based on the theory of slightly curved crack fronts predicts that fatigue crack growth is enhanced if the applied stress intensity factor is greater than the fracture toughness of the particles. In the other case, the crack front advances in the matrix before it can traverse the particles (crack pinning). Below a certain stress intensity factor, the crack is completely arrested by the particles causing a fatigue threshold. The predictions are compared with experiments on Al alloys. Limitations of the linear perturbation theory are discussed.